The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14020379
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Structure and Properties of Biofunctional Keratin from Rabbit Hair

Abstract: Keratin is widely recognized as a high-quality renewable protein resource for biomedical applications. A large amount of rabbit hair waste is produced in textile industries, because it has high medullary layer content, but poor spinnability. Therefore, it is of great significance to extract keratin from waste rabbit hair for recycling. In this research, an ultrasonic-assisted reducing agent-based extraction method was developed and applied to extract keratin from rabbit hair. The results showed that the ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Untreated wool (spectrum 1) records the following absorption bands: 3296 cm −1 (N-H and O-H), 2877 cm −1 (-CH 2 ), 1607 cm −1 (Amide I), 1527 cm −1 (Amide II), and 1244 cm −1 (Amide III). This information is close to that indicated in the literature [28][29][30]. The functionalization of the wool by protonation (spectrum 2) determines changes only at the level of the absorption bands of the free NH 2 groups that become + NH 3 (according to Equation (3)).…”
Section: Functionalization Of Betalainssupporting
confidence: 88%
“…Untreated wool (spectrum 1) records the following absorption bands: 3296 cm −1 (N-H and O-H), 2877 cm −1 (-CH 2 ), 1607 cm −1 (Amide I), 1527 cm −1 (Amide II), and 1244 cm −1 (Amide III). This information is close to that indicated in the literature [28][29][30]. The functionalization of the wool by protonation (spectrum 2) determines changes only at the level of the absorption bands of the free NH 2 groups that become + NH 3 (according to Equation (3)).…”
Section: Functionalization Of Betalainssupporting
confidence: 88%
“…The Shindai method was selected for the extraction of human hair keratin, as this method yields α- keratin and does not use any detergents [ 16 ]. The scaffold that was developed using a 1:3 and 1:4 ratio of keratin and PVA formed a continuous porous composite scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…The same tendency can be seen for ESPE with lower molecular weight compared to PRO and a slightly higher average particle size (293 nm compared to 334 nm) and lower zeta potential (−23.3 mV compared to –28.5 mV, respectively). The results showed that the performed hydrolyses were not as destructive for the keratin molecule as those reported for the enzymatic hydrolysates when the average particle size was reported to be 100–150 nm [ 36 ], but comparable to those of 750 nm, tested as a bioactive and biocompatible material for wound healing [ 34 ]. The self-assembling ability of keratin hydrolysate was also highlighted for keratin hydrolysates extracted by keratinase use [ 34 ] or by ultrasound assisted chemical extraction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%